Photosynthesis, Dry Matter Partitioning and Yield Variation in Sesame Genotypes - Akter, M; Khaliq, QA; Islam, MR; Ahmed, JU (Bangladesh Agronomy Journal, 2016)
An experiment was conducted at the research field of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur-1706 from March to June 2014 to evaluate growth and yield performance of sesame genotypes. Five sesame genotypes i.e. DB-6992, BD-6995, BD-7001, BD-7011 and Hathazari-4 were used in the study. The genotypes significantly differed in photosynthetic rate, dry matter partitioning and seed yield. The earliest genotype was Hathazari-4 and the latest was BD-7011. The highest stem dry weight, leaf dry weight, capsule dry weight, leaf area index, light interception, photosynthetic rate were recorded in genotype Hathazari-4. The number of capsules plant-1 and the number of seeds capsule-1 were also highest in the genotype Hathazari-4, while the lowest was being noticed in the genotype BD- 7001. Weight of 1000-seed was the maximum in genotype BD-6992 and the minimum in the genotype BD- 7011. The highest seed yield (3.52 tha-1) was recorded in the genotype Hathazari-4 and the lowest in the genotypes BD-6992 followed by BD-7001. The highest oil content (41.39%) was recorded in the genotype BD-6992 and the lowest (39.72%) in the genotype Hathazari-4 but the highest oil yield (1.53 t ha-1) was recorded in the genotype Hathazari-4. It may be concluded that the sesame genotype Hathazari-4 may be cultivated for higher seed yield and oil production. Bangladesh Agron. J. 2016, 19(1): 19-28